2017
DOI: 10.15611/pn.2017.463.12
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Benefits Arising From the Implementation of Management Processes in Terms of Enterprises Maturity

Abstract: Streszczenie: Koncepcji, metod, narzędzi usprawniających funkcjonowanie przedsiębiorstwa jest bardzo wiele, jednakże zawsze istnieje niepewność co do skuteczności nowych rozwiązań. W artykule podjęto próbę analizy i oceny korzyści wynikających z wdrożenia podejścia procesowego, skupiając uwagę na możliwych zależnościach. W związku z powyższym jako cel badawczy przyjęto ustalenie zależności występujących pomiędzy stopniem wdrożenia podejścia procesowego a oceną korzyści wynikających z jego implementacji. Inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Zarządzanie Nr 34 (2019) s. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] dostępne na: http://www.wz.pcz.pl/znwz jako wielopoziomowe struktury pozwalające użytkownikowi transformować określone informacje wejścia na pożądane informacje wyjścia za pomocą odpowiednich procedur i modeli (Kiełtyka 2001, s. 200-202). W zmiennym otoczeniu modelowanie optymalnych zespołów zadaniowych skutecznie realizujących procesy usługowe czy produkcyjne wymaga modyfikacji hierarchicznych i tworzenia elastycznych, horyzontalnych struktur organizacyjnych.…”
Section: Zeszyty Naukowe Politechniki Częstochowskiejunclassified
“…Zarządzanie Nr 34 (2019) s. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] dostępne na: http://www.wz.pcz.pl/znwz jako wielopoziomowe struktury pozwalające użytkownikowi transformować określone informacje wejścia na pożądane informacje wyjścia za pomocą odpowiednich procedur i modeli (Kiełtyka 2001, s. 200-202). W zmiennym otoczeniu modelowanie optymalnych zespołów zadaniowych skutecznie realizujących procesy usługowe czy produkcyjne wymaga modyfikacji hierarchicznych i tworzenia elastycznych, horyzontalnych struktur organizacyjnych.…”
Section: Zeszyty Naukowe Politechniki Częstochowskiejunclassified
“…• no empirical results have been identified that would suggest which factors are most strongly correlated with critical performance dimensions (Ha-Brookshire, Jung 2009) • in "high-performance enterprises", belonging to the SME sector, the level of efficiency is monitored using a wide range of efficiency indicators; however, the study described in the literature lacked a detailed description of the research tool, evaluation model and a set of indicators measuring efficiency (Zbierowski 2013) • the relationship between the efficiency measurement and the accuracy of the performance measurement has been recognised by scientists around the world (Koźmiński 2008;Koźmiński and Latusek-Jurczak 2017) • system and the development efficiency of small and medium-sized enterprises was confirmed (Gębczyńska, 2017) ENTREPRENEURSHIP AND SUSTAINABILITY ISSUES ISSN 2345-0282 (online) The hypotheses formulated complement the proposed research questions: HP0: A statistically significant reciprocal relationship exists between the model elements and the efficiency. HP1: The efficiency between the distinguished types of activity differs significantly.…”
mentioning
confidence: 99%
“…In the traditional approach, the efficiency measures turned out to be insufficient for managing small organisations (Gębczyńska 2017). A mere increase in economic efficiency is not enough to change the overall use of resources.…”
mentioning
confidence: 99%